Entrepreneurial events across the world : which ones fit in Portugal? - Vacas, Ana de Mira Borges da Mota (2018)
This thesis was developed as part of a consulting project for Beta-i’s event department. The purpose was the study of events targeting particularly startups and entrepreneurs promoted in five specific locations: Macao, Hong Kong, China, Singapore and Kenya. This because Beta-i aimed at better getting to know these regions’ ecosystems and the type of events promoted there. Furthermore, the company also wished to be shown event formats and/or topics it wasn’t yet developing. To provide the company with a proper and thorough analysis, the first step was to validate the companies that promoted entrepreneurial events and only then the events themselves. This analysis led to the conclusion that Beta-i already promoted several event formats found in the locations studied, however some suggestions could still be made. The first suggestion was to develop Workshops on topics like digital marketing, the path to success, business optimization and growth, legal issues and how to handle stress. Other ideas were the Learn, meet & speak events, Startup job fairs, Info sessions, Thank God it Failed, and Ecosystem bridging events. The results of the study also uncovered the possibility of merging some of the event formats found abroad with, for example, the TGIF series in Beta-i’s portfolio, in an attempt to increase attendance and reduce costs. A general structure of all the events found was presented, together with an estimation of the costs. In the end, recommendations for further study include looking into countries such as Kazakhstan, Taiwan, India, Israel and the United Arab Emirates.